AGUIAR AGUILAR, Maravillas; CABO GONZÁLEZ, Ana María; MONFERRER-SALA, Juan Pedro (coords.). Labore et constantia. Estudios andalusíes: ensayos selectos. Colección de Estudios Árabo-Islámicos de Almonaster la Real, 22. Córdoba: UCOPress. Editorial Universidad de Córdoba, Editorial Universidad de Sevilla, Servicio de Publicaciones. Universidad de La Laguna, 2022. 784 páginas: ilustraciones (blanco y negro y color); 25 cm. ISBN UCOPress: 978-84-9927-706-6. ISBN Editorial Universidad de Sevilla: 978-84-4722375-6. ISBN Servicio de Publicaciones. Universidad de la Laguna: 978-84-167471-22-5. D.L.: CO 1048-2022. - MEDINA, Ana María (Al-Andalus Magreb, 2024)
The volume "Labore et Constantia" is a compilation that includes twenty-six essays and an annex, mostly aimed at Andalusian issues, all preceded by a preliminary section dedicated to evaluating and recognizing the work and academic trajectory of María Arcas Campoy, professor of Arab and Islamic Studies at the University of La Laguna and a prominent figure in the field of study of Islamic law and the history and society of al-Andalus.